KEPEMIMPINAN KEPALA DESA DALAM URUSAN KEPENDUDUKAN DI DESA TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR TAHUN 2018-2019 - Ahmad Rezky; Sofyan Hadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to look at the leadership of the Tarai Bangun Village Head in population affairs (update the address on the family card according to the Tarai Bangun Village address) and the factors that influence the number of Tarai Bangun Village people who do not want to update the address on their family card according to the Tarai Bangun Village address. This study uses the theory of government leadership techniques from S. Pamudji, namely information, human relations, being an example, persuasive, using a suitable communication system, and providing facilities. This study uses a descriptive approach with a qualitative type, then the data collection techniques used are interviews, observation and documentation, while the data analysis technique is done by collecting information through interviews. The results of this study indicate that the leadership of the Tarai Bangun Village Head in population affairs is quite good, because it has fulfilled all the techniques proposed by S. Pamudji. In the form of direct appeals, explaining facts, meeting community needs, providing facilities. Be a role model, and use a suitable communication system, although there are still some obstacles in improving the orderly population data in the village of Tarai Bangun such as; The amount of cost and time required, the number of people working in Pekanbaru, the lack of sensitivity of the previous government to the community, and the community's perception of the Tarai Bangun Village that will be expanded resulted in many people being reluctant to change their population data to the address of Tarai Bangun Village so that the efforts made have not been fully achieved. Keywords: Information, Human Relations, Example, Persuasive Command, Adaptive, facility provider